Suboptimal Femoral Component Size after Oxford Unicompartmental Knee Arthroplasty: Does it Affect Clinical Outcome? - Wen-Shuo Chang; Kuan-Ting Chen; Tsung-Mu Wu; Chin-Wei Lin; Chung-Han Ho; Chien-Cheng Huang; Chi-Sheng Chien (Formosan Journal of Musculoskeletal Disorders)
Background: Oxford unicompartmental knee arthroplasty (OUKA) is a reliable surgical procedure for anteromedial osteoarthritis of the knee. However, inconsistent outcomes are still found across studies. Imperfect femoral component size is an implant factor that may lead to poor outcome such as bearing dislocation or persistent pain. However, in Taiwan, the incidence and clinical outcomes in patients with suboptimal femoral component size remain unclear. Objectives: This study aims to clarify the incidence and clinical outcomes in patients with suboptimal femoral component size. Materials and Methods: We identified all patients receiving OUKA in a Taiwan medical center between 2018 and 2021 for this study. Age, sex, height, weight, body mass index, pre- and postoperative Knee Society Score (KSS) functional activity score, and postoperative range of motion (ROM) and Numeric Rating Scale (NRS) were included. Optimal and suboptimal groups were classified based on the posterior fit of the femoral component on postoperative lateral radiography. Outcome comparisons were performed between the two groups after follow-up. Results: Ninety-two patients (111 knees) were included in the study, including 79 (71.2%) knees in the optimal group and 32 (28.8%) knees in the suboptimal group. The median age was 68 years and 67 years, and the percentage of the male sex was 17.7% and 37.5% in the optimal and suboptimal groups, respectively. Compared with the suboptimal group, there was a greater improvement in KSS functional activity score in the optimal group; however, the difference was not significant (40 vs. 34, P = 0.154). Nonsignificant differences were also found between the two groups in the postoperative KSS functional activity score and the postoperative NRS and ROM. Conclusions: Our study showed that the suboptimal femoral component size does not significantly affect short-term clinical outcome. Further studies with more patients and longer follow-up time are needed for long-term outcome validation.